2014
DOI: 10.1051/ject/201446197
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating the Systemic Inflammatory Response to Adult Cardiopulmonary Bypass: A Critical Review of the Evidence Base

Abstract: A wide range of pharmacological, surgical, and mechanical pump approaches have been studied to attenuate the systemic inflammatory response to cardiopulmonary bypass, yet no systematically based review exists to cover the scope of anti-inflammatory interventions deployed. We therefore conducted an evidence-based review to capture “self-identified” anti-inflammatory interventions among adult cardiopulmonary bypass procedures. To be included, trials had to measure at least one inflammatory mediator and one clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(14 citation statements)
references
References 123 publications
0
14
0
Order By: Relevance
“…26 Therefore, limiting the inflammatory response has been an important myocardioprotective intervention during CPB. 26 Clearly, an improved understanding of the molecular mechanism underlying CPB-associated ferroptosis is key to improving myocardioprotective strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Therefore, limiting the inflammatory response has been an important myocardioprotective intervention during CPB. 26 Clearly, an improved understanding of the molecular mechanism underlying CPB-associated ferroptosis is key to improving myocardioprotective strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has previously been demonstrated that CPB induces a systemic inflammatory response 24,25 linked to adverse clinical outcomes ranging from mild adverse effects to severe complications and death. 26 Therefore, limiting the inflammatory response has been an important myocardioprotective intervention during CPB. 26 Clearly, an improved understanding of the molecular mechanism underlying CPB-associated ferroptosis is key to improving myocardioprotective strategies.…”
Section: Discussionmentioning
confidence: 99%
“…52 Previous reviews have concluded that no one single intervention used in isolation shows strong evidence in preventing inflammation. Landis et al 82 have proposed a “multiple hit” hypothesis whereby to achieve clinically effective suppression of the immune system required hitting multiple inflammatory targets. 82…”
Section: Introductionmentioning
confidence: 99%
“…Landis et al 82 have proposed a “multiple hit” hypothesis whereby to achieve clinically effective suppression of the immune system required hitting multiple inflammatory targets. 82…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that a dysregulated systemic inflammatory response is associated with organ dysfunction (5, 6), as exemplified by the relationship between cytokine levels and the occurrence and severity of acute kidney injury (AKI) (7–9). To date, no pharmacologic interventions are licensed to limit systemic inflammation or protect renal function (10–13).…”
mentioning
confidence: 99%